2014
DOI: 10.1073/pnas.1317360111
|View full text |Cite|
|
Sign up to set email alerts
|

Natural variation of rice strigolactone biosynthesis is associated with the deletion of two MAX1 orthologs

Abstract: Significance Strigolactones are a new class of plant hormones regulating plant shoot and root architecture in response to the environment. Also present in root exudates, strigolactones stimulate the germination of parasitic plant seeds. This report describes a genomic polymorphism—associated with the Indica / Japonica subspecies divide in rice that has a major impact on the biosynthesis of strigolactones, plant tillering, and germination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 49 publications
4
97
1
Order By: Relevance
“…Another rice MAX1 homolog, Os1400, then converts ent-2′-epi-5-deoxystrigol into orobanchol . Rice has five MAX1 orthologs, of which fourOs900, Os1400, Os5100 and Os1900 -were shown to rescue the Arabidopsis max1 mutant phenotype (Challis et al 2013;Cardoso et al 2014). Although upon expression in Nicotiana benthamiana Os5100 and Os1900 catalysed the conversion of carlactone into ent-2′-epi-5-deoxystrigol (and minute amounts of 5-deoxystrigol), this occurred with very low efficiency, just as for Arabidopsis MAX1 .…”
Section: Sl Biosynthesis and Signallingmentioning
confidence: 99%
“…Another rice MAX1 homolog, Os1400, then converts ent-2′-epi-5-deoxystrigol into orobanchol . Rice has five MAX1 orthologs, of which fourOs900, Os1400, Os5100 and Os1900 -were shown to rescue the Arabidopsis max1 mutant phenotype (Challis et al 2013;Cardoso et al 2014). Although upon expression in Nicotiana benthamiana Os5100 and Os1900 catalysed the conversion of carlactone into ent-2′-epi-5-deoxystrigol (and minute amounts of 5-deoxystrigol), this occurred with very low efficiency, just as for Arabidopsis MAX1 .…”
Section: Sl Biosynthesis and Signallingmentioning
confidence: 99%
“…Among SL synthesis components, D27 encodes a β-carotene isomerase that converts all-trans-β-carotene into 9-cis-β-carotene (13,14). MAX3/RMS5/D17/DAD3 and MAX4/RMS1/D10/DAD1 encode the carotenoid cleavage dioxygenase 7 (CCD7) and CCD8, leading to the formation of carlactone, which is catalyzed further by MAX1/OsMAX1 to yield SL compounds (12,15,16). For the SL signaling components, MAX2/RMS4/D3 encodes an F-box protein participating in SL perception (17)(18)(19), D14/DAD2 encodes a protein of the α/β-fold hydrolase superfamily, a proposed SL receptor (20)(21)(22)(23)(24)(25), and D53 encodes a Clp protease family protein as a repressor (26,27).…”
mentioning
confidence: 99%
“…After the discovery of the first root-derived germination stimulants, Butler (1995) coined the name strigolactones (SLs) for these strigol-related compounds. So far, a variety of different SLs have been isolated from a range of plant species, and it has been shown that exudates contain more than one strigolactone and differences in the composition exist even between varieties of one species (Awad et al, 2006;Xie et al, 2010;Cardoso et al, 2014).…”
Section: Host Finding and Orientation: The Key Role Of Strigolactonesmentioning
confidence: 99%